2023
DOI: 10.3390/su15020975
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Human Resources for Development and Innovation, Science Transformation into Industry Infrastructure by China’s New Universities: A Case Study of Green Materials

Abstract: The connection of universities with new knowledge in various sciences leads to entrepreneurship and the progress of the economic development of universities. Countries with higher education institutions, in the shadow of practical research and development, are trying to strengthen the economic structure and entrepreneurship, and conduct basic research. Besides, higher education institutions are building science parks and implementing high-tech projects jointly with industry. New materials such as PVC and concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Moreover, the research endeavors to bridge the gap in empirical understanding by exploring the correlation between applied undergraduate education in data science and regional economic development. By doing so, the study aspires to contribute to the broader goal of enhancing universities' capabilities to serve regional economic and social development, while simultaneously fostering innovation-driven progress in the dynamic field of data science [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the research endeavors to bridge the gap in empirical understanding by exploring the correlation between applied undergraduate education in data science and regional economic development. By doing so, the study aspires to contribute to the broader goal of enhancing universities' capabilities to serve regional economic and social development, while simultaneously fostering innovation-driven progress in the dynamic field of data science [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at present, the production of ordinary concrete of classes C35/45 to C50/60 no longer poses major technological problems for concrete-mixing plants and precast concrete plants [12,13]. Therefore, it can be concluded that the concrete produced today is a material with much better parameters than the one produced only a few decades ago [14,15].…”
Section: Introductionmentioning
confidence: 99%